Foaming behaviour and cell structure of poly(lactic acid) after various modifications. Issue 5 (14th September 2012) - Yu, Long; Toikka, Gary; Dean, Katherine; Bateman, Stuart; Yuan, Qiang; Filippou, Con; Nguyen, Tri
Abstract: Improving the melt strength of poly(lactic acid) (PLA) is of continuing strategic research interest since a low melt strength results in poor processability of foaming and blowing film. PLA was modified in various ways including crosslinking, chain extension, grafting, blending, plasticizing and nucleation to improve its melt strength. This work focuses on the effect of melt strength after various modifications on foaming behaviour and cell structures of PLA foam. Cell density was increased and cell structure became more uniform with increasing melt strength, in particular when the melt strain was also increased after modification. With increasing melt strength the phenomenon of open and ruptured cells was decreased. The foaming window was widened with increasing melt strength, in particular after crosslinking, chain extension and blending with elastomer. Molecular weight, thermal properties and viscosity of PLA after various modifications were also studied and used to explain the foaming behaviour and foam structures. Copyright © 2012 Society of Chemical Industry Abstract : Cell density was increased and cell structure became more uniform with increasing melt strength, in particular when the melt strain was also increased after modifications (crosslinking, chain extension, grafting, blending).